Post-locked down mental wellbeing among Malaysian adults: factors of life satisfaction in urban Malaysia - Kususanto Ditto Prihadi; Daryll Kurian; Grace Jee Ern Nga; Endah Kurniawati Purwaningtyas (International Journal of Public Health Science (IJPHS), 2022)
Under the enforcement of the recovery movement control order (RMCO), citizens of Malaysia were allowed to commute for work with tight protocols of social distancing. In this period of time, most individuals were adjusting to the new norm after being locked down for about six weeks. With an assumption that the social dynamics could have been different from the pre-pandemic era, this study aims to investigate how mattering predicts life satisfaction among individuals who live in the urban area of western Malaysia in the aforementioned timeframe. The role of other variables, namely perceived social support (PSS), resilience, and spirituality was also investigated. Data was collected from 402 adults between 18 and 66 years of age (M=25.44) who reside in the urban areas of Malaysia. A moderated serial mediation hypothesis was tested by employing the Bootstrap method in PROCESS Macro model 92. Our findings suggested that resilience does not play a significant role in the equation due to its insignificance in predicting life satisfaction after controlling the rest of the variables.